Langerhans cell histiocytosis as an unusual cause of back pain in a child: A case report and review of literature - Balachandran, Hemaswetha (J Craniovertebr Junction Spine, 2017)
Low back pain in children and adolescents are usually attributed to mechanical causes and faulty positions. Although most of them are self-limiting, physicians should be aware of the red flag signs that warrant complete evaluation to rule out malignant causes of back pain. As delay in the diagnosis of vertebral lytic lesion may have sequelae in the growing children, pain disproportionate to the signs should have low threshold levels for evaluation. We report a case of 6-year-old boy who presented with worsening back pain. Initially evaluated for tuberculosis spine, he was diagnosed to have Langerhans cell histiocytosis of spine. He improved symptomatically with chemotherapy and spine orthosis and is in complete remission now.